2019
DOI: 10.1093/europace/euz116
|View full text |Cite
|
Sign up to set email alerts
|

Long-term single-centre large volume experience with transseptal endocardial left ventricular lead implantation

Abstract: Aims The aim of our study was to investigate the long-term efficacy and safety of transseptal endocardial left ventricular lead implantation (TELVLI). Methods and results Transseptal endocardial left ventricular lead implantation was performed in 54 patients (44 men, median age 69, New York Heart Association III–IV stage) between 2007 and 2017 in a single centre. In 36 cases, the transseptal puncture (TP) was performed via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Most studies demonstrated significant improvements in LV remodeling and favorable clinical response to CRT; however, its procedural complexity and substantial long-term thromboembolic risk limit wider adoption. [16][17][18][19] The ALSYNC (Alternate Site Cardiac Resynchronization) was the first multicenter trial of LV endocardial transvenous lead pacing (superior transvenous atrial transseptal approach), which enrolled 138 patients who either had a failed transvenous CS lead or had nonresponse to CRT. 20 The procedure was successful in 118 of the 132 attempted cases (89%).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies demonstrated significant improvements in LV remodeling and favorable clinical response to CRT; however, its procedural complexity and substantial long-term thromboembolic risk limit wider adoption. [16][17][18][19] The ALSYNC (Alternate Site Cardiac Resynchronization) was the first multicenter trial of LV endocardial transvenous lead pacing (superior transvenous atrial transseptal approach), which enrolled 138 patients who either had a failed transvenous CS lead or had nonresponse to CRT. 20 The procedure was successful in 118 of the 132 attempted cases (89%).…”
Section: Discussionmentioning
confidence: 99%
“…His Bundle pacing 12 has proven useful in selected patients. Intravascular techniques in which a lead is directed trans‐septally to the left atrium and then through the mitral valve to the left ventricular endocardium (eg, ALSYNC protocol) 13 require continuous anticoagulation during follow‐up, but thrombo‐embolic events have been fairly common, 13,14 which may limit widespread acceptance of the method. Alternative methods for epicardial pacing are more invasive and include surgical approaches by thoracoscopy and various forms of mini‐thoracotomy 1‐3 .…”
Section: Discussionmentioning
confidence: 99%
“…При оценке рисков вмешательства с имплантацией ЛЖ электрода через МПП учитывается возможность травматизации створок митрального клапана. Однако, данных за подтверждение данной патологии исследователи не приводят, и даже наоборот, имеются результаты обследований, где уровень митральной регургитации снижается [31]. С использованием методики по имплантации ЛЖ электрода через МЖП имеются риски развития транссептальных токов крови в месте пункции и желудочковых тахикардий, что также в проведённых исследованиях не было подтверждено.…”
Section: Discussionunclassified
“…В публикации T.R.Betts et al 2018 года описывается развитие лакунарного ишемического инсульта и ТИА у 3-х из 15-ти пациентов за период от 6 недель до 3-х лет после оперативного вмешательства [19]. Также, в недавно опуб ликованном исследовании L.Gellér et al 2019 года описывается развитие тромбоэмболических осложнений у 4-х из 54-х пациентов (7%) на фоне терапии антагонистами витамина К, однако, при обследовании выяснилось, что уровень МНО у всех пациентов был ниже целевого (2,5) [31].…”
Section: Discussionunclassified